Mitigating Residual Tropospheric Delay to Improve User’s Network-Based Positioning - Musa, Tajul A.; Wang, Jinling; Rizos, Chris; Lee, Young-Jin; Mohamed, Azhari (2004)
Existing apriori tropospheric models are not sufficiently accurate to remove tropospheric delay from GPS observations. Remaining effects of residual tropospheric delay need to be estimated to ensure high accuracy and reliability of GPS positioning. Other researchers have shown that implementations of network-based positioning techniques can adequately model the residual tropospheric delay as well as ionospheric delay and orbit biases. However, the effectiveness in removing residual tropospheric delay is highly dependent on the degree to which the wet component from the troposphere can be estimated or mitigated, an effect which shows strong variation with time and space. The aim of this paper is to illustrate the performance of an existing apriori tropospheric model and to discuss some issues concerning the estimation of the (total) tropospheric delay in the equatorial area. Finally, the network approach is applied to mitigate the effect of residual tropospheric delay. Some preliminary results from test experiments using GPS network data from an equatorial region, a location with the highest effect of tropospheric delay, are presented.